PROFIL MINAT KARIR SISWA KELAS IX YANGORANG TUANYA PETANI DAN PEDAGANG DI SMP NEGERI 5 TANAH PUTIH TAHUN 2013/ 2014 - Yusuf, Sardi Yusuf Sardi; Arlizon, Raja Arlizon Raja; ', Rubiati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : The title of this research is a Career Interest Profile Class IX students whose parents Farmers and traders in Tanah Putih SMP Negeri 5 Year 2013/2014, the main problem in this study how the picture Career Interest Profile Class IX students whose parents Farmers and traders in SMP Negeri 5 White ground. The purpose of this research is to describe Interests Karis Grade IX whose parents Farmers and traders in SMP Negeri 5 Tanah Putih and to know embodiment in future planned by the students in determining what options are in sanggupi students according to their parents. The benefits of this research are expected as input for teachers in an effort to achieve national education goals and inputs for the instasi associated and involved in national education. survey is a research technique to provide boundary in the form of data, investigation, evaluation. Interest is the tendency of the soul to something that is accompanied by feelings of pleasure would be something. Career interests is one of the most important things to prepare for success in the future especially in this Globasisasi age. Regular career interests achieved in various ways one of his schooling. According Suharsimi Arikunto (1997: 4) states that the educational process there are five factors that influence are: 1. Teachers and other Personal 2. Study materials, 3. Methods of teaching and evaluation systems, support and advice 4. 5. System Administration. The fifth factor in the school environment. Factors that influence the career interests of students are supported with their parents professions are: Willingness, perseverance, achievement motivation and unyielding. The assumption of this study were all students have an interest in different careers and career interests are affected by the environment and outside the school, teachers and playmates. The population in this study is a class IX students of SMP Negeri 5 Soil samples were collected by White and distribute the data to the sisiwa to be examined. This research is a real research because these students are berkecimpungan therein that aims to identify career interests of students of class IX that the parents are farmers and traders in SMP Negeri 5 White Land. The type of data in this study are primary data directly obtained through questionnaires or questionnaires. Keywords:StudentCareerInterests